Stress Fracture of the Second Metatarsal and Sprain of Lisfranc Joint in a Pre-Professional Ballet Dancer. Issue 2 (June 2015) - Kriz, Peter; Rafferty, Jason; Evangelista, Peter; Van Valkenburg, Scott; DiGiovanni, Christopher
We present the case of a 14-year-old preprofessional ballerina that demonstrates common features of two conditions affecting the midfoot that are often missed or subject to delay in diagnosis in such young athletes: 1. stress fractures at the base of the second metatarsal, and 2. sprain of the Lisfranc joint complex. While these represent potentially career-altering injuries in the professional dancer, this case demonstrates that a high index of clinical suspicion, careful physical exam, appropriate radiographic assessment, and prompt treatment are essential to achieving the best possible outcome.